The social state re-visited - García Belaunde, Domingo (2011)
During the 19th century, a form of State was developed that was presented in more or less peaceful terms and without further questioning. It was spoken or understood as something natural of a reality such as "Rule of Law" or "Liberal State" or "Liberal State of Law". In a somewhat exaggerated way, they wanted to typify this model with the rather graphic letterhead of “Policy State”. Others had described him as a "night watchman." In any case, what lay behind all these conceptualizations is that the State needed certain limits that it could not exceed. And this main idea was the one that - starting from the French Revolution - promoted a State model that spread widely throughout the 19th century.